Fifteen new polymorphic microsatellite loci for the meadow brown butterfly, Maniola jurtina. (December 2015) - Richard, Murielle; Villemey, Anne; Stevens, Virginie M.; Blanvillain, Gaelle; Dardenne, Sophie; Baguette, Michel
Abstract: We characterized fifteen microsatellite markers for the butterfly Maniola jurtina . For the six studied populations (96 samples) the total number of alleles per locus ranged from 3 to 55 and mean overall expected heterozygosity across all loci was 0.74. In spite of a high frequency of null alleles detected in part of the loci, a recurrent phenomenon in Lepidopteron, the estimation of pairwise FST seems rather insensitive to the presence of these null alleles as shown by the high correlation between FST calculated after correction for the presence of null alleles and non-corrected FST, indicating that the loci may be usable in population genetics, more specifically for the study of populations genetics structure. Highlights: Fifteen microsatellite markers for the butterfly Maniola jurtina . 3 to 55 alleles per locus, mean overall expected heterozygosity across loci of 0.74. Pairwise FST rather insensitive to null alleles high frequency, common in butterflies. Loci may be usable for the study of populations genetics structure.